Lanthanide conjugates as versatile instruments for therapy and diagnostics - Herlan, Claudine; Bräse, Stefan (Dalton transactions, 2020)
Lanthanides have demonstrated outstanding properties in many fields of research including biology and medicinal chemistry. Their unique luminescence and magnetic properties make them the metals of choice for next generation theranostics that efficiently combine the two central pillars of medicine - diagnostics and therapy. Attached to targeting units, lanthanide complexes pave the way for real-time imaging of drug uptake and distribution as well as specific regulation of subcellular processes with few side effects. This enables individualized treatment options for severe diseases characterized by altered cell expression. The highly diverse results achieved as well as insights into the challenges that research in this area has to face in the upcoming years will be summarized in the present review.